Mahasiswa KKN Membersamai dalam Mengembangkan Nilai Pendidikan Keagamaan Di Desa Tanjung Rusa - Iskandi, Iskandi (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2023)
The research in this article describe an effrot student work together in developing the value of religious education in Tanjung Rusa Village. This research is presented in the form of descriptive qualitative data . As for looking at how the work program is implemented regarding the benefits of students for society which is realized through moving together with the community in developing the value of religious education in the form of teaching at the Al-Quran education park (TPA), Teaching reading and writing the Al-Quran , teaching PAUD, and celebrating the PHBI birthday of the prophet SAW. This was done because saw that the teaching staff was still lacking in teaching in Tanjung Rusa Village. With this movement, it was finally possible to increase the value of religious education in the village . and the community is enthusiastic about taking part in the activities carried out to develop the value of religious education . Penelitian pada artikel ini memaparkan sebuah upaya mahasiswa membersamai dalam mengembangkan nilai pendidikan keagamaan di Desa Tanjung Rusa. Yang mana penelitian ini disajikan dalam bentuk data kualitatif deskriptif. Adapun melihat dari bagaimana pelaksanaan program kerja berkenaan dengan kebermanfaatan mahasiswa untuk masyarakat yang diwujudkan melalui bergerak bersama masyarakat dalam mengembangkan nilai pendidikan keagamaan berupa mengajar di Taman Pendidikan Al-Qur’an (TPA), Mengajar baca tulis Al-Qur’an, Mengajar PAUD, dan Merayakan PHBI Maulid Nabi Saw. Hal tersebut dilakukan karena melihat keadaan tenaga pengajar masih kurang dalam mengajar di Desa Tanjung Rusa. Denganpergerakan tersebut akhirnya mampu meningkatkan nilai pendidikan keagamaan di desa tersebut. Dan Masyarakatpun antusias untuk mengikuti kegiatan yang dilakukan dalam mengembangkan nilai pendidikan keagamaan tersebut,